2005
DOI: 10.1021/ja0507719
|View full text |Cite
|
Sign up to set email alerts
|

Sol−Gel Materials as Efficient Enzyme Protectors:  Preserving the Activity of Phosphatases under Extreme pH Conditions

Abstract: By entrapment in (surfactant modified) silica sol-gel matrixes, alkaline phosphatase (AlP) -- naturally with optimum activity at pH 9.5 -- was kept functioning at extreme acidic environments as low as pH 0.9, and acid phosphatase (AcP) -- naturally with optimum activity at pH 4.5 -- was kept functioning at extreme alkaline environments, up to pH 13.0. Propositions are offered as to the origin of the ability of the matrixes to provide such highly efficient protection and as to the origin of the synergetic enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
126
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(135 citation statements)
references
References 36 publications
7
126
0
2
Order By: Relevance
“…Complementary to genetic modifications such as directed evolution [9] and site mutation [10], chemical modification via conjugation or encapsulation provide an efficient route to preserve enzyme stability under harsh conditions. Different coating materials have been tested including silica [11], polymers [12,13] and organo-clay. These coating materials, however, may hinder the conformational transition of the enzyme and the transport of substrate, resulting in low biocatalytic activity.…”
mentioning
confidence: 99%
“…Complementary to genetic modifications such as directed evolution [9] and site mutation [10], chemical modification via conjugation or encapsulation provide an efficient route to preserve enzyme stability under harsh conditions. Different coating materials have been tested including silica [11], polymers [12,13] and organo-clay. These coating materials, however, may hinder the conformational transition of the enzyme and the transport of substrate, resulting in low biocatalytic activity.…”
mentioning
confidence: 99%
“…Finally we note that the reaction between the olefin and the bromine solution yields the by-product, hydrobromic acid, which lowers the pH [22], and we already described protection against pH changes elsewhere [16].…”
Section: Exposure Of the Entrapped Enzyme To Bromine And Determinatiomentioning
confidence: 51%
“…Thus, the hybrid sol-gel material we used was based on vinyl (CH 2 =CH-Si; VTS; here and below we use the name of the monomer as the name of the material), or allyl (CH 2 =CH-CH 2 -Si; ATS). In earlier studies we showed these olefinated sol-gel materials are highly reactive towards bromine, undergoing in water an hydrobromination reaction [16,17] which proceeds according to Markovnikov's rule [18], as shown in Scheme 1, resulting in a bromohydrin and HBr. The formation of an acid is an environmental change that the entrapped enzyme can withstand.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Alkaline phosphatase, encapsulated in silica gels either in the absence or presence of the surfactants sodium bis(2-ethylexyl) sulfosuccinate (AOT) and cetyltrimethylammoniumbromide (CTAB) [184], exhibited a three-fold decrease in the turnover number with respect to the enzyme in solution, whereas the enzyme is still active at pH 2.4 and pH 13, where the enzyme in solution is inactive. AOT more than CTAB protects the enzyme against the extreme pH conditions.…”
Section: Kinases and Phosphatasesmentioning
confidence: 99%